1999
DOI: 10.1152/ajplung.1999.277.6.l1158
|View full text |Cite
|
Sign up to set email alerts
|

Human lung myofibroblast-derived inducers of alveolar epithelial apoptosis identified as angiotensin peptides

Abstract: Earlier work from this laboratory found that fibroblasts isolated from fibrotic human lung [human interstitial pulmonary fibrosis (HIPF)] secrete a soluble inducer(s) of apoptosis in alveolar epithelial cells (AECs) in vitro [B. D. Uhal, I. Joshi, A. True, S. Mundle, A. Raza, A. Pardo, and M. Selman. Am. J. Physiol. 269 (Lung Cell. Mol. Physiol. 13): L819-L828, 1995]. The cultured human fibroblast strains most active in producing the apoptotic activity contained high numbers of stellate cells expressing alpha-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
103
0
4

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(114 citation statements)
references
References 28 publications
7
103
0
4
Order By: Relevance
“…Several pericellular factors may contribute to this dysregulated communication. AEC apoptosis/necrosis adjacent to underlying ␣-smooth muscle actin-expressing myofibroblasts has been demonstrated (20); this effect may involve the secretion of angiotensin-II by myofibroblasts (36). In addition, myofibroblastdifferentiated cells are potent generators of extracellular ROS, specifically hydrogen peroxide (37).…”
Section: What Are the Cellular And Molecular Mechanisms For Injury/apmentioning
confidence: 99%
“…Several pericellular factors may contribute to this dysregulated communication. AEC apoptosis/necrosis adjacent to underlying ␣-smooth muscle actin-expressing myofibroblasts has been demonstrated (20); this effect may involve the secretion of angiotensin-II by myofibroblasts (36). In addition, myofibroblastdifferentiated cells are potent generators of extracellular ROS, specifically hydrogen peroxide (37).…”
Section: What Are the Cellular And Molecular Mechanisms For Injury/apmentioning
confidence: 99%
“…The local synthesis of Ang II has been demonstrated in lung fibrotic plaques, where it is produced by activated myofibroblasts and probably impacts the survival of other neighboring cells (Uhal, 2002;Wang et al, 1999). We investigated the effect of Ang II on bovine PAECs using the neutral comet assay, which detects chromosomal breakdown as a function of apoptosis.…”
Section: Ang-ii-induced Apoptosis Requires the At2 Receptormentioning
confidence: 99%
“…Blockade of Ang-II signaling, either by using inhibitors of angiotensinconverting enzyme to prevent Ang-II maturation or using antagonists of Ang-II cellular receptors, can abrogate the development of fibrosis in animal models in the lung, liver, kidney and heart (Bataller et al, 2005;Dendorfer et al, 2005;Konigshoff et al, 2007;Sun, 2009;Wolf, 2008). In a number of fibrotic diseases, local synthesis of Ang II has been observed, and fibroblasts from the diseased tissues of human patients were found to generate Ang II (Bader, 2002;Sun et al, 2000;Wang et al, 1999). Two primary events are associated with the development and progression of fibrosis: (1) the transdifferentiation of fibroblasts into the activated fibroblast (myofibroblast) phenotype that secretes abnormal extracellular-matrix proteins such as collagens I and III (Wynn, 2008); and (2) apoptosis of the normal epithelial and endothelial cells of the tissues (Marshall, 2003;Wang et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…1), noradrenaline (NA) [18] and angiotensin (ANG)II [19,20]. The latter is particularly important because in vitro studies have demonstrated that ANGII, synthesised de novo by the AEC, is required as a mediator of the apoptotic response to Fas activation, to TNF-a, amiodarone, NA [15][16][17][18], and possibly other inducers [9].…”
Section: Apoptosis In the Alveolar Epitheliummentioning
confidence: 99%
“…With regard to human lung, the author has also shown that myofibroblasts derived from lung biopsies obtained from patients with IPF produce and secrete ANG peptides, and on this basis it was hypothesised that local ANG production is key in both initiating and "propogating" the fibrotic focus [20].…”
Section: Angiotensin and Lung Fibrosismentioning
confidence: 99%